Javanese Cultural Dynamics and the Halal Industry: A Systematic Literature Review - Wimpow Panjaitan; Heru Kurnianto Tjahyono; Claudius Budi Santoso (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The interaction of culture, particularly Javanese culture, with the halal industry is a unique topic, as it examines how long-held traditional values adapt to modern developments within the halal industry, which has an Islamic identity. More comprehensive research is needed, gathering perspectives from relevant literature related to Javanese culture and the halal industry. Therefore, this study aims to gather various literature and its developments, while analyzing them to identify key themes, identify research gaps, and provide possible future research directions. The Systematic Literature Review (SLR) method, using the PRISMA program using the Watase UAKE program, was chosen to achieve the research objectives. The research results demonstrated the relevance and validity of 47 articles out of 142 Scopus articles. The publication trend for "Javanese culture and the halal industry" has increased significantly since 2022. The main theme of Javanese culture is reflected in the keyword "Javanese culture," while in the halal industry, it is reflected in the keywords "halal industry" and "halal food." A variety of holistic and comprehensive approaches to understanding the dynamics of Javanese culture and the halal industry is needed to address various research gaps in the previous literature. Therefore, in the future, mixed-methods research will be the best choice, utilizing various theories, including Cultural Integration Theory.